2014
DOI: 10.4103/0255-0857.129812
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adhesive genes among uropathogenic Escherichia coli strains isolated from patients with urinary tract infection in Mangalore

Abstract: The study was carried out to detect the adhesive genes pap (pyelonephritis associated pili), sfa (S fimbrial adhesin) and afa (afimbrial adhesin) from Escherichia coli strains isolated in patients diagnosed with urinary tract infection (UTI). A total of 23% of the isolates were positive for pap, sfa and afa genes with a prevalence of 60.87% (14/23), 39.1% (9/23) and 39.1% (9/23), respectively. Prevalence of multiple adhesive genes was 8.7% (2/23) for pap and afa, 30.43% (7/23) for pap and sfa. Significant numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
3
15
0
1
Order By: Relevance
“…The higher number of samples having pap and sfa genes together as compared with other combinations could be due to the localization of these genes on the same pathogenicity island of UPEC strains [36]. In our study, the combination of pap/sfa genes was more frequently detected than pap/afa genes, which is similar to previous studies [36,37]. Cellular morphology and molecular biology studies have revealed that UPEC express siderophore production peculiar to the strains of E. coli causing extraintestinal infections [38].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The higher number of samples having pap and sfa genes together as compared with other combinations could be due to the localization of these genes on the same pathogenicity island of UPEC strains [36]. In our study, the combination of pap/sfa genes was more frequently detected than pap/afa genes, which is similar to previous studies [36,37]. Cellular morphology and molecular biology studies have revealed that UPEC express siderophore production peculiar to the strains of E. coli causing extraintestinal infections [38].…”
Section: Discussionsupporting
confidence: 88%
“…In another study by Usein et al, the prevalence rates of fimH, sfa/foc, papC, and afa in Romanian adults with UTI was 86%, 23%, 36%, and 14%, respectively [35]. The higher number of samples having pap and sfa genes together as compared with other combinations could be due to the localization of these genes on the same pathogenicity island of UPEC strains [36]. In our study, the combination of pap/sfa genes was more frequently detected than pap/afa genes, which is similar to previous studies [36,37].…”
Section: Discussionmentioning
confidence: 94%
“…The sfa gene was found in twelve (70.6 %) of the isolates together with pap genes. Shetty et al (2014) explained that co-existence of these two genes are due to their localization on the same pathogenicity island of UPEC strains 30 . In addition, most of the isolates carried multiple adhesion genes, indicating A and D groups in each population can vary according to various factors (geographic/climatic conditions, dietary factors, the use of antibiotics, host genetic factors) and commensal strains can acquire virulence factors and become potentially pathogenic 37 .…”
Section: Determination Of Antimicrobial Resistance and Virulencementioning
confidence: 99%
“…In the present study, we found very high frequency of the sfa gene in the hospitalized RUTIs patients, where all the isolates were positive in PCR amplification. Previous studies have concluded that more than 50% of the sfa1 + isolates of E. coli in the UTIs have a high prevalence of virulence factors and pose a serious threat to the health of the patients (28). Adhesion and fimbrial virulence factors in E. coli such as sfa, afa, fim, etc., cause further risks in the development of RUTIs, especially in women (29).…”
Section: Discussionmentioning
confidence: 99%